2012
DOI: 10.1007/s13592-011-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Queen mandibular pheromone: questions that remain to be resolved

Abstract: -The discovery of 'queen substance', and the subsequent identification and synthesis of key components of queen mandibular pheromone, has been of significant importance to beekeepers and to the beekeeping industry. Fifty years on, there is greater appreciation of the importance and complexity of queen pheromones, but many mysteries remain about the mechanisms through which pheromones operate. The discovery of sex pheromone communication in moths occurred within the same time period, but in this case, intense p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 156 publications
(153 reference statements)
0
10
0
Order By: Relevance
“…Obp1 interacts with the main component of queen mandibular pheromone (QMP; Pesenti et al 2008). QMP influences the behavior and physiology of workers in several ways including delaying behavioral maturation and reducing JH biosynthesis (reviewed in Jarriault and Mercer 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obp1 interacts with the main component of queen mandibular pheromone (QMP; Pesenti et al 2008). QMP influences the behavior and physiology of workers in several ways including delaying behavioral maturation and reducing JH biosynthesis (reviewed in Jarriault and Mercer 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesized benefit to the bee society from this blocking effect is the neutralization of any unpleasant perception of the high levels of QMP. This idea is supported by the observation that only very young bees are attracted to the queen, whereas older nurses and foraging individuals are repelled by QMP (Jarriault and Mercer, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…Studies by Mercer and colleagues have revealed that dopamine plays a critical role in social communication via the peripheral modulation of worker bee responses to the queen mandibular pheromone (QMP) (Beggs et al, 2007; Vergoz et al, 2007). A plausible mechanism by which the queen bee influences the colony is via QMP components such as homovanillyl alcohol, which structurally resembles dopamine (Jarriault and Mercer, 2012). One hypothesized benefit to the bee society from this blocking effect is the neutralization of any unpleasant perception of the high levels of QMP.…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees, like many insects, employ a rich repertoire of pheromones to ensure intraspecific communication in many behavioural contexts [ 19 , 31 33 ]. In the context of mating, the major compound of the queen mandibular pheromone (QMP), 9-oxo-2-decenoic acid (9-ODA), which also participates in communicating the queens’ fertility within the hive [ 31 , 34 , 35 ], attracts drones over long distances [ 36 40 ]. It possibly acts together with secondary components also involved in the communication between queens and workers [ 41 ].…”
Section: Introductionmentioning
confidence: 99%